2016
DOI: 10.1038/srep24196
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HCCR expression resensitizes gastric cancer cells to chemotherapy via down-regulating the activation of STAT3

Abstract: The human cervical cancer oncogene (HCCR) has been found to be overexpressed in a variety of human cancers. However, the level of expression of HCCR and its biological function in gastric cancer are largely unknown. In this study, we evaluated HCCR expression in several gastric cancer cell lines and in one normal gastric mucosal cell line. We established a 5-FU-resistant gastric cancer cell subline, and we evaluated its HCCR expression. HCCR expression levels were high in gastric cancer lines, and expression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In gastric cancer, suppressing the activation of STAT3 resensitized cells to chemotherapy (27). Inhibition of STAT3 has influence on cell cytotoxic and cytostatic effect, it also reinforces anticancer immunosurveillance to increase therapeutic efficacy and stem cell-like phenotype (28). In human Wilms tumor SK-NEP-1 cells, inhibiting STAT3 and CDDP reduced cell growth in vivo (29).…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer, suppressing the activation of STAT3 resensitized cells to chemotherapy (27). Inhibition of STAT3 has influence on cell cytotoxic and cytostatic effect, it also reinforces anticancer immunosurveillance to increase therapeutic efficacy and stem cell-like phenotype (28). In human Wilms tumor SK-NEP-1 cells, inhibiting STAT3 and CDDP reduced cell growth in vivo (29).…”
Section: Discussionmentioning
confidence: 99%
“…2 showed a stronger efficiency than others. However, complete suppression of LETMD1 expression caused inhibition of proliferation as described previously in various cancer cells (5,7,8). Therefore, we chose cells with shRNA no.…”
Section: Suppression Of Letmd1 Expression Causes Enhancement In Lps-imentioning
confidence: 97%
“…In contrast, silencing of LETMD1 results in a decrease in cell survival and proliferation via the promotion of p53, p21, and Bax expression (7). In addition, LETMD1 expression is positively associated with the phosphorylation of STAT3, which is associated with cellular proliferation and resistance to chemotherapy in gastric cancer (8). A previous report demonstrated that LETMD1 is localized at the mitochondrial outer membrane as a membrane-bound protein, and it has been implicated in resistance to UV and staurosporine-induced apoptosis, which might be caused by mitochondrial dysfunction (9).…”
mentioning
confidence: 99%
“…For example, IL‐6 and IL‐11 are important regulatory factors in the process of inflammation leading to cancer development, and they may promote tumor aggressiveness correlating with patients’ survival time . STAT3 and NF‐κB activation, which causes gastric cancer progression and leads to enhanced cellular proliferation, is also correlated with poor survival . Currently, STAT3 inhibitors are emerging as a promising drug for gastric cancer .…”
Section: Introductionmentioning
confidence: 99%